HUBUNGAN PENGETAHUAN TENTANG PERAWATAN PAYUDARA DENGAN PERILAKU DALAM PERAWATAN PAYUDARA PADA IBU NIFAS - Rahayu, Tri Budi; Ernawati, Evy (MEDIA ILMU KESEHATAN, 2020)
Background:The production of breast milk which is less and slowly exits can cause the mother not to give enough milk to her baby. In addition to the hormone prolactin, the lactation process also depends on the hormone oxytocin, which is released from posterior pituitary as a reaction to nipple sucking. Oxytocin affects the myoepithelial cells that surround the alveoli so that the alveoli contracts and secretes milk that has been secreted by the mammary gland, this oxytocin reflex is affected by the mother's soul. If there is anxiety, stress and hesitation that occurs, then the expenditure of breast milk can be hampered. Various ways can be done to stimulate the oxytocin reflex. The endorphin massase method is used as an alternative way to provide comfort for labor pain and can increase the release of oxytocin substances.Objective:This study aims to determine the effect of endorphin massage on breastfeeding in postpartum mothers.Methods:This study was quasi experimental with a sample of postpartum mothers. The independent variable is endorphin massage, and the dependent variable is breastfeeding with a post test only design with control group design. The statistical test used was the Wilcoxon test.Results:Based on the results of research conducted on 20 respondents, the results obtained from the non parametric statistical test 2 indepedence samples (Wilcoxon test) stated that the results of the Wilcoxon statistical test showed results p = 0.026 <0.05, meaning Ho was rejected and HÄ± was accepted so that there was influence oxytocin massage against the time of milk removal.Conclusion:There is an effect of oxytocin massage on the time of breastfeeding in postpartum mothers.